2022
DOI: 10.3390/plants11243460
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Activity of Papaloquelite (Porophyllum ruderale) in Thioacetamide-Induced Injury Model

Abstract: Acute kidney injury and impaired kidney function is associated with reduced survival and increased morbidity. Porophyllum ruderale is an edible plant endemic to Mexico used in Mexican traditional medicine. The aim of this study was to evaluate the nephroprotective effect of a hydroalcoholic extract (MeOH:water 70:30, v/v) from the aerial parts of P. ruderale (HEPr). Firstly, in vitro the antioxidant and anti-inflammatory activity of HEPr was determined; after the in vivo nephroprotective activity of HEPr was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…TAA is a powerful hepato- and nephrotoxic agent that is widely used to establish a reproducible model of acute liver and kidney injury [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. OA is a penta-cyclic triterpene that exists in free or glycosidic forms with one or more sugar moieties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TAA is a powerful hepato- and nephrotoxic agent that is widely used to establish a reproducible model of acute liver and kidney injury [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. OA is a penta-cyclic triterpene that exists in free or glycosidic forms with one or more sugar moieties.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in serum creatinine indicates leakage from necrotic cells or its biosynthesis upregulation. BUN reflects the accumulated urea amount that is not effectively excreted due to kidney impairment [ 5 , 37 ]. In this study, TAA injection affected hepatic and kidney function as presented by elevated levels of serum transaminases, creatinine, and BUN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This meta-analysis included 18 research with 278 animals (Chander et al, 2005;Kusumoto et al, 2011;Sanchez-Gonzalez et al, 2011;Nabavi et al, 2012;Saito et al, 2014;Li et al, 2016;Gholampour and Sadidi, 2018;Shu et al, 2018;Tan et al, 2019;Tan et al, 2020;El-Sayed et al, 2021;Goncalves et al, 2021;Rahdar et al, 2021;Wang et al, 2020;Ali et al, 2022;Vazquez-Atanacio et al, 2022;Yilmaz et al, 2022). The result showed that quercetin administration obviously decreased BUN (SMD = −4.78; 95% CI: 6.45, −3.12; p < 0.01; I 2 = 84%) in AKI animals (Figure 2A).…”
Section: Blood Urea Nitrogenmentioning
confidence: 98%
“…After reading the full-text articles, 55 studies were excluded due to 1) the animal model not being correct, 2) data not being clear, 3) duplicate data, and 4) the original text not being available. Finally, 19 studies were eligible in which 288 animals were included (Chander et al, 2005;Kusumoto et al, 2011;Sanchez-Gonzalez et al, 2011;Nabavi et al, 2012;Chen et al, 2014;Saito et al, 2014;Li et al, 2016;Gholampour and Sadidi, 2018;Shu et al, 2018;Lucida et al, 2019;Tan et al, 2019;Tan et al, 2020;El-Sayed et al, 2021;Goncalves et al, 2021;Rahdar et al, 2021;Wang et al, 2020;Ali et al, 2022;Vazquez-Atanacio et al, 2022;Yilmaz et al, 2022) (Figure 1). Frontiers in Pharmacology frontiersin.org Frontiers in Pharmacology frontiersin.org…”
Section: Study Selectionmentioning
confidence: 99%